Super excitements and their relationship with parental treatment methods among a sample of talented students in the intermediate stage in Taif city in light of some variables. - Almalki; Saad Essa, Saeed (International Journal of Psychosocial Rehabilitation, 2023)
The study aimed to identify the overexcitability and its relationship to parental treatment among middle school gifted students in the city of Taif in the light of some variables.class, number of brothers and sisters and monthly income. A available sample of 100 middle school students in the city of Taif was tested, and the questionnaire was relied upon as a tool for the study. The data is then analysed using t. test. The result indicate that a relationship found between overexcitability and parental treatment. Also, no difference found in these two variables in terms in, Classes, and monthly income. The results were then discussed in the context of suadi culture. Recommendation for further research was made